PENGETAHUAN IBU HAMIL TENTANG BAHAYA ROKOK TERHADAP PERKEMBANGAN JANIN DI DESA KUTA PARIK KECAMATAN SELESAI KABUPATEN LANGKAT - Kristin Natalia (JURNAL ILMIAH DHDT - KEBIDANAN, 2019)
Results of data from Indonesia women who smoke about 2.3%, while in pregnant women around 1.7% , from this data has proven to increase the likelihood of pregnant women who smoke will cause various complications of pregnancy danger signs such as premature birth, premature birth weight, perinatal mortality and fetal development disorders. This type of research is descriptive, that is by using primary data obtained using a questionnaire containing 20 statements made by the researchers themselves. The samples in this study 20 of 30 people, taken by purposive sampling. From the results of the study it was obtained the results that the majority of respondents were knowledgeable as many as 10 respondents (50%), knowledgeable Enough as many as 7 respondents (35%) while the minority of knowledgeable good as many as 3 respondents (15%). The researcher hopes that respondents will add insight and input knowledge and information about the dangers of smoking to fetal development.